The Influence Of Organizational Learning On Improving The Accreditation Of Public Health Kubutambahan I And Public Health Sawan I In Buleleng District - Bali - Gede Ivan Kresnayana (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The Accreditation Process is still a frightening specter at every Puskesmas. Accreditation is a benchmark for extrenal quality assurance at each puskesmas through Organizational Learning efforts. The study aims to analyze the Effect of Organizational Learning on Improving Accreditation of Kubutambah I Health Center and Sawan I Health Center in Buleleng Regency - Bali. The method used is a mix method, observational research type with cross-sectional approach. The population in this study involved 2 Community Health Centers namely Kubutambah 1 and Sawan 1 with 100 respondents with a purposive sampling technique. The research instrument used a questionnaire with closed questions that had a valid and reliable test of 0.6. Data analysis used in the study was a logistic regression statistical test with α 0.05. Analysis of Kubutambahn I Public Health Center and Sawan I Public Health Center in Buleleng Regency showed that out of 100 respondents or information from 2 health centers there were Organizational Learning in the good category of 62% and 38% not good. good category 98% and not good as much as 2%, the relationship between Organizational Learning and the performance of accreditation of puskesmas in Buleleng Regency with a p-value of 0.047, which means it is smaller than α 0.05 so there is an influence of Learning Organization on accreditation. There is the effect of Organizational Learning on the performance of accreditation at Kubutambahn I Puskesmas and Sawan 1 Puskesmas in Buleleng Regency